Should Counselors Teach? - Andrews, Gerald R. (Canadian Journal of Counselling and Psychotherapy, 1972)
A position paper which considers an important aspect of the counselor's working conditions. The point was made that pre-requisite to a productive consideration of the question Should Counselors Teach? is agreement upon the role of the counselor to be discussed. Two typical roles were contrasted, and one was selected as the focus for discussion of the main question. Consistent with the selected role, 11 principles of school guidance and counseling which are satisfactory for the 1970's were stated. It was found that the question of part-time or full-time counseling is inseparable from the matters of role, preparation, selection, status, and accountability of counselors. Support was given to the proposition that only the full-time counselor can satisfactorily carry out the selected role.